How binding are the EU's 'binding' renewables targets? - Johnston, A; Van Der Marel, E (Cambridge University Press, 2016)
The EU's current renewable energy legislation sets a binding EU target for renewables as a share of overall energy consumption, allied with binding national targets for renewables as well. Yet the precise implications of having imposed such 'mandatory' binding targets have received little attention to date. This contribution examines the history and evolution of such targets, the context within which they must be pursued and applied, and some of the problems in and prospects for their enforcement and effectiveness. Comparisons are drawn with other areas of EU law where appropriate and some tentative lessons learned, as well as challenges still to be faced, are offered by way of conclusion.